Pengaruh Pemberian Ekstrak Etanol Daun Sambiloto( Andrographis paniculata Nees) Terhadap Histopatologi Pankreas Mencit ( Mus musculus ) Diabetes Melitus (DM) Tipe I - Dwielma C. Nubatonis; Nemay Anggadewi Ndaong; Yulfia Nelymalik Selan (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Diabetes mellitus (DM) is a metabolic disorder which damage the beta cells (β) which led to the destruction of langerhans of pancreas gland. Diabetes mellitus is characterized by increased blood glucose levels and progressive changes to the structure of the histopathology of the pancreas. The purpose of this study was to determine the effect of ethanol extract of sambiloto leaf ( Andrographis paniculata Nees) on pancreatic histopathology of Alloxan induced diabetic mice. This research is an experimental research design by Post Test Randomized Control Group Design Experim ental animals used were mice ( Mus musculus) 12 sample of mice ±2 weeks old were adapted for 5 days. Mice were divided into 4 groups, namely, negative control, positive contro l (3 days of alloxan injection) and diabetic mice treated with the ethanol extract of sambiloto leaf with 2 different doses (doses I =2,2mg/kg and dosesII=4,4mg/kg) for 14 days. On day15, mice were necropsy and pancreas were collected for further Hematoxiline Eosin (HE) coloration. The results showed that DM alloxan induced type 1 mice (Mus musclus), the pancreas characterized by the occurrence of necrosis, langerhans islet was not bounded clear and breakthe linkage of the langerhans islet with a cinar while on ethanol extract therapy of sambiloto leaf dose 2,2 mg/kg and 4,4 mg/kg in mice DM type I showed the results an improvement on the langerhans islet. Based on these results, it can be concluded that a dose of 2,2 mg/kg and 4,4 mg/kg is effective dose to repair the structure of langerhans islet of mice Type I DM, but it is more adv isable to us a therapeutic dose of 4,4 mg/kg because it changes the structure of Langerhans islet.